KORELASI USIA DAN PARITAS TERHADAP PENGGUNAAN ALAT KONTRASEPSI - Nukuhaly, Hasnawati; Saptaningrum, Epi; Multazam, Andi Muhammad; Lestari, Wa Ode Sri Wati; Martini, Titin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The choice of modern contraceptive methods in Central Java province in 2023, the majority chose the injection method 37.9% and other methods such as implants 9.7%, pills 3.4%, male condoms 2.9% and those who did not use birth control amounted to 28.6%. The purpose of the study was to determine the correlation of age and parity on the use of contraceptives. The study used quantitative research with case control design. The research was conducted at Pringapus Health Center. The research was conducted in November 2023. The study population was all married mothers in the working area of Pringapus Health Center. The sample amounted to 70 people. The sampling technique used purposive sampling. Data analysis was done univariate and bivariate. The results showed there was a relationship between parity (p value: 0.035) to the selection of contraceptive methods. It is suggested that respondents can consider using contraceptive implants because this contraceptive has advantages such as effectively preventing pregnancy between three years, is not permanent and does not need to be consumed every day or used before sexual intercourse.Keywords: Contraception, Parity, Health Center.